Principles of therapeutic exercise for the physical therapist assistant - Kopack, Jacqueline Klaczak PT, DPT; Cascardi, Karen A. PhD, MS, ATC, PTA (Thorofare, NJ SLACK Incorporated, 2023)
"Principles of Therapeutic Exercise for the Physical Therapist Assistant is a textbook that provides PTA educators, PTA students, and practicing PTA clinicians with a guide to the application of therapeutic exercise across the continuum of care.Written by two seasoned clinicians with more than 40 years of combined PTA education experience, Principles of Therapeutic Exercise for the Physical Therapist Assistant focuses on developing the learners' ability to create effective therapeutic exercise programs, as well as to safely and appropriately monitor and progress the patient within the physical therapy plan of care. The content is written in a style conducive to a new learner developing comprehension, while still providing adequate depth as well as access to newer research.Included in Principles of Therapeutic Exercise for the Physical Therapist Assistant are:Skill competency outlines, worksheets and problem-solving rubricsIndications, contraindications, and red flags associated with various exercise interventionsDocumentation tipsEasy-to-follow tables to aid in understanding comprehensive treatment guidelines across the phases of rehabilitation "Eye on the Research" sections throughout the text dedicated to current research and evidence-based practicesAlso included with the text are online supplemental materials for faculty use in the classroom, consisting of PowerPoint slides and an instructor's manual (complete with review questions and quizzes).Created specifically to meet the educational needs of PTA students, faculty, and clinicians, Principles of Therapeutic Exercise for the Physical Therapist Assistant is an exceptional, up-to-date guidebook that encompasses the principles of therapeutic science across the entire continuum of care"--
Chapter 1. Introduction to therapeutic exercise -- Chapter 2. Implementing a therapeutic exercise program -- Chapter 3. Injuries, tissue healing, and surgical interventions -- Chapter 4. Range of motion and manual therapy techniques -- Chapter 5. Stretching and flexibility -- Chapter 6. Principles of muscle strengthening and performance -- Chapter 7. Posture, pregait and gait training interventions -- Chapter 8. Balance training and vestibular rehabilitation -- Chapter 9. Aerobic conditioning -- Chapter 10. Aquatic therapy -- Chapter 11. Orthopedic considerations -- Chapter 12. Therapeutic exercise for the upper extremity -- Chapter 13. Management of lower extremity orthopedic conditions -- Chapter 14. Management of cervical and thoracic spine orthopedic conditions -- Chapter 15. Lumbar spine and sacroiliac joint: common diagnoses and orthopedic management -- Chapter 16. Exercise considerations for persons with neurological exercise -- Chapter 17. Therapeutic exercise considerations after lower extremity amputation -- Chapter 18. Pulmonary conditions and treatment interventions -- Chapter 19. Physical therapy interventions for persons with an oncologic and/or lymphedema diagnosis -- Chapter 20. Exercise for the medically complex patient -- Chapter 21. Pelvic floor and women's health exercises -- Chapter 22.Workplace rehabilitation, ergonomics and safety -- Chapter 23. Considerations for athletes
Includes bibliographical references and index
Keywords: Exercise; Physical therapy -- Practice